2017
DOI: 10.1128/jb.00810-16
|View full text |Cite
|
Sign up to set email alerts
|

ThiN as a Versatile Domain of Transcriptional Repressors and Catalytic Enzymes of Thiamine Biosynthesis

Abstract: Thiamine biosynthesis is commonly regulated by a riboswitch mechanism; however, the enzymatic steps and regulation of this pathway in archaea are poorly understood. Haloferax volcanii, one of the representative archaea, uses a eukaryote-like Thi4 (thiamine thiazole synthase) for the production of the thiazole ring and condenses this ring with a pyrimidine moiety synthesized by an apparent bacterium-like ThiC (2-methyl-4-amino-5-hydroxymethylpyrimidine [HMP] phosphate synthase) branch. Here we found that archae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Based on the riboswitch mechanism, mutations in the genes of thiamine pyrophosphate kinase activity (thiN) and thiamine-related transport proteins (YkoD and YuaJ) were introduced in B. subtilis TH95. It was recently reported that thiamine biosynthesis is strictly regulated by TPP riboswitches in bacteria/eukaryotes and transcriptional repressors in archaea (Hwang et al, 2017). E. coli has emerged as the preferred cell factory for TPP production after a riboswitch-based biosensors enabled the discovery of thiamine transporters, combined with overexpression of the native thiFSGHCE and thiD genes, which are closely related to Fe-S metabolism (Figure 1A and Table 1; Cardinale et al, 2017).…”
Section: Vitamin Bmentioning
confidence: 99%
“…Based on the riboswitch mechanism, mutations in the genes of thiamine pyrophosphate kinase activity (thiN) and thiamine-related transport proteins (YkoD and YuaJ) were introduced in B. subtilis TH95. It was recently reported that thiamine biosynthesis is strictly regulated by TPP riboswitches in bacteria/eukaryotes and transcriptional repressors in archaea (Hwang et al, 2017). E. coli has emerged as the preferred cell factory for TPP production after a riboswitch-based biosensors enabled the discovery of thiamine transporters, combined with overexpression of the native thiFSGHCE and thiD genes, which are closely related to Fe-S metabolism (Figure 1A and Table 1; Cardinale et al, 2017).…”
Section: Vitamin Bmentioning
confidence: 99%
“…ThiC (HMP-P synthase; EC 4.1.99.17) is the major enzyme used by bacteria [40,41], plant chloroplasts [42] and archaea [43] to synthesize the aminopyrimidine ring of thiamine (Figures 2-4).…”
Section: Synthesis and Phosphorylation Of The Aminopyrimidine Ring Of...mentioning
confidence: 99%
“…ThiD homologs (IPR004399) are widespread in all domains of life, including organisms that only salvage HMP and do not synthesize thiamine de novo. Archaeal ThiD proteins are standalone or fused to a ThiN-type ThMP synthase domain (see later discussion) [43,53,54].…”
Section: Synthesis and Phosphorylation Of The Aminopyrimidine Ring Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…Its genome has been sequenced and carefully annotated [ 1 , 10 , 11 ]. A plethora of biological aspects have been successfully tackled in this species, with examples including DNA replication [ 4 ]; cell division and cell shape [ 12 , 13 , 14 , 15 , 16 ]; metabolism [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]; protein secretion [ 26 , 27 , 28 , 29 ]; motility and biofilms [ 30 , 31 , 32 , 33 , 34 , 35 ]; mating [ 36 ]; signaling [ 37 ]; virus defense [ 38 ]; proteolysis [ 39 , 40 , 41 , 42 , 43 , 44 ]; posttranslational modification (N-glycosylation; SAMPylation) [ 45 , 46 , 47 , 48 , 49 , 50 ]; gene regulation [ 21 , 25 , 51 , 52 , 53 , 54 , 55 ]; microproteins [ 56 , 57 , 58 ] and small noncoding RNAs (sRNAs) […”
Section: Introductionmentioning
confidence: 99%